1995
DOI: 10.1016/0014-5793(95)01243-9
|View full text |Cite
|
Sign up to set email alerts
|

FAD is a further essential cofactor of the NAD(P)H and O2‐dependent zeaxanthin‐epoxidase

Abstract: dase was suggested to be associated with the stromal side of this membrane [16]. Recently, Zea epoxidation activity was attributed to isolated LHCsII [19,20].In this study we demonstrate that a further cofactor, flavin adenine dinucleotide (FAD), is involved in the NAD(P)H-and O2-dependent epoxidation of Zea. Presumable, one part of the protein-associated flavin moiety is lost during the isolation procedure of the thylakoid membranes and consequently the epoxidase activity is attenuated. Addition of FAD to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 36 publications
(30 reference statements)
2
57
0
Order By: Relevance
“…This localization suggests that the envelope membranes (containing ZEP but not VDE) could be the site of violaxanthin biosynthesis whereas the thylakoid membranes (with both ZEP and VDE) would be the site of the xanthophyll cycle ( Figure 6). In isolated thylakoid membranes, ZEP was found to be a multi-component FAD-containing monooxygenase (Büch et al, 1995), consistent with the presence of a FAD-binding domain in the enzyme (Marin et al, 1996). Mutants defective in ZEP activity were isolated in a screening for ABA-deficient mutants (named aba1) and shown to produce significantly lower ABA levels than the wild type (Koornneef et al, 1982;Rock and Zeevaart, 1991 Data were obtained using the Arabidopsis Coexpression Tool ACT (http://www.arabidopsis.leeds.ac.uk/act/ coexpanalyser.php).…”
Section: Xanthophyll Cycle Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…This localization suggests that the envelope membranes (containing ZEP but not VDE) could be the site of violaxanthin biosynthesis whereas the thylakoid membranes (with both ZEP and VDE) would be the site of the xanthophyll cycle ( Figure 6). In isolated thylakoid membranes, ZEP was found to be a multi-component FAD-containing monooxygenase (Büch et al, 1995), consistent with the presence of a FAD-binding domain in the enzyme (Marin et al, 1996). Mutants defective in ZEP activity were isolated in a screening for ABA-deficient mutants (named aba1) and shown to produce significantly lower ABA levels than the wild type (Koornneef et al, 1982;Rock and Zeevaart, 1991 Data were obtained using the Arabidopsis Coexpression Tool ACT (http://www.arabidopsis.leeds.ac.uk/act/ coexpanalyser.php).…”
Section: Xanthophyll Cycle Enzymesmentioning
confidence: 99%
“…Because the carotenoid desaturases PDS and ZDS use plastoquinone as hydrogen acceptor, their activity is connected to the photosynthetic electron transport chain (Carol and Kuntz, 2001). Both PDS and ZDS, as well as other carotenoid biosynthetic enzymes such as CRTISO, LCYB, LCYE, and ZEP, contain a conserved FADbinding motif that suggests the involvement of redox balance in the corresponding enzymatic reactions (Hugueney et al, 1992;Büch et al, 1995;Marin et al, 1996;Schnurr et al, 1996;Isaacson et al, 2004;Mialoundama et al, 2010;Yu et al, 2010;Yu et al, 2011). There is also evidence for a redox control of the expression of some carotenoid biosynthetic genes in tobacco chloroplasts and tomato fruit chromoplasts (Woitsch and Römer, 2003;Nashilevitz et al, 2010).…”
Section: Modulation Of Enzyme Levels and Activitiesmentioning
confidence: 99%
“…This is the case in lycopene b-cyclase, which was active in vitro only in the presence of NADH or NADPH (Schnurr et al, 1996), and carotenoid isomerase, which was dependent on redox driving force (Isaacson et al, 2004). Involvement of FAD in ZEP activity has also been demonstrated (Buch et al, 1996). It has been recently demonstrated that the bacterial lycopene cyclase (CRTY) requires a reduced FAD as a catalytic cofactor probably for stabilization of a transition state in an acid-base reaction (Yu et al, 2010).…”
Section: Involvement Of Orr In the Carotenoid Biosynthetic Pathwaymentioning
confidence: 99%
“…One phytochemical compound, b-ionone, an end ring analog of b-carotenoid, represents a subclass of cyclic isoprenoids. Physiological functions attributed to b-ionone include the inhibition of the growth of fungi 7 and the regulation of the synthesis of mevalonate-derived constituents. 8 In previous studies, b-ionone inhibited the growth of breast-, gastric-, colon-and HL-60-cancer cells in a dosedependent manner, [9][10][11][12][13] affected the MAPK pathway of MDA MB 435 cells, 14 and induced apoptosis of SGC-7901 gastric cancer cells and B16 murine tumor cells.…”
mentioning
confidence: 99%